Influence of recreational activities as work stress coping strategies among female academic staff in University of Lagos (2017)
Stress is known to have deleterious effects on human motivations and strive to accomplish life ambition in conquering the environment, human performance, health and psycho-physiologically wellbeing. This study examined the influence of recreational activities as work stress level coping strategies among female academic staff in University of Lagos. It aimed at addressing the issue on how work stress can be effectively managed, reduced or prevent through recreational activities in order to enhance health and improve personal and work behaviours of the female academic staff of the University of Lagos. Descriptive survey research method was adopted for this study. Two hundred permanent female academic staff was randomly selected from 12 faculties. The instrument for the study was self-developed. Three hypotheses were formulated and tested in the study using chi-square (x2) and Pearson r correlation statistical technique at 0.05 level of significance. Based on these findings, it was concluded that certain situational variables were significantly correlate of stress among female academic staff in the University of Lagos. Therefore, it is recommended that female academic staff should endeavor to create time to exercise regularly, get enough sleep, learn to relax, eat healthfully, managing time and finances and reduce work stress